The Behavior Management Dilemma With Student Teachers: a Practical Perspective from the Field - Robert Wolfersberger (The Advocate, 2011)
A significant contributor to student misbehavior is unskilled teacher behaviors. This article identifies some of these counterproductive teaching behaviors that unintentionally create a learning environment vulnerable to student misbehavior. Student teachers are in the process of developing their skills and if they are not equipped with a functional behavior management plan and the accompanying application skills, their students may become victims of inappropriate consequences. Skill in managing student behavior is an essential teacher tool. The author recommends a practical approach to behavior management for student teachers that gives proper focus and emphasis to this important and sensitive subject.